Cultivation of corneal endothelial cells from sheep. (August 2018) - Al Abdulsalam, Najla Khaled; Barnett, Nigel L.; Harkin, Damien G.; Walshe, Jennifer
Abstract: Research is currently under way to produce tissue engineered corneal endothelium transplants for therapeutic use in humans. This work requires the use of model animals, both for the supply of corneal endothelial cells (CECs) for experimentation, and to serve as recipients for test transplants. A variety of species can be used, however, a number of important advantages can be gained by using sheep as transplant recipients. The purpose of the present study was therefore to develop a method for culturing sheep CECs that would be suitable for the eventual construction of corneal endothelium grafts destined for sheep subjects. A method was established for culturing sheep CECs and these were compared to cultured human CECs. Results showed that cultured sheep and human CECs had similar growth characteristics when expanded from corneal endothelium explants on gelatin-coated plates, and achieved similar cell densities after several weeks. Furthermore, the markers zonula occludens-1, N-cadherin and sodium potassium ATPase could be immunodetected in similar staining patterns at cell boundaries of cultured CECs from both species. This work represents the first detailed study of sheep CEC cultures, and is the first demonstration of their similarities to human CEC cultures. Our results indicate that sheep CECs would be an appropriate substitute for human CECs when developing methods to produce tissue engineered corneal endothelium transplants. Highlights: Sheep and human corneal endothelial cell cultures are highly similar. Sheep corneal endothelial cells express characteristic markers in vitro. Small, compact corneal endothelial cells form next to explants in culture.